Substantial Feasibility of Implementing the Merdeka Curriculum: Analysis of Teachers’ Teaching Perspectives in Elementary School - Reviandy Azhar Ramdhani; Yuniar Mujiwati; Ayu Maya Damayanti; Khamdan Safiudin; Nur Kholis (Program Studi PGSD Universitas Madako Tolitoli, 2024)
The implementation of the Merdeka Curriculum aims to ensure common understanding in improving the quality of education at all levels of education. This curriculum model underscores fostering students' independence, creativity, and learning skills, positioning students as active learners. Assessing the understanding of teachers and students as respondents' representation of the implementation of the Merdeka Curriculum at SDN Warungdowo 1 is the main objective of this study. Mixed responses from respondents who revealed the substantial feasibility of implementing the curriculum and acknowledged its flexibility in tailoring the learning experience to student needs, challenges remain, including inadequate training, support, resource constraints, and curriculum adjustments are the findings of this study. Overcoming these hurdles requires additional support through the provision of resources and teacher training. In addition, encouraging effective collaboration between schools, educators, students, parents, and government is essential to strengthen the effectiveness of the Merdeka Curriculum. The contribution of research provides a comprehensive understanding of the application of the Merdeka Curriculum which is essential in improving the effectiveness of adapting curriculum policies that are not partial in the context of learning in elementary schools.